The Influence of Family and Religion on Youth Decisions in Higher Education English Literature Review - Ostafiński, Witold (Edukacja • Terapia • Opieka, 2022)
The literature review explores the influence of family and religion on youth decisions in higher education. The study examines articles on how parental influence and religion impact the youth’s horizons of actions. The research identified three significant influencers linked to academic performance and college readiness: parental figures, educators and peers. Parental influence has become an emergent factor in enrolling in higher education. Parental guidance and experience can impact willingness to enroll in higher education and highlight the importance of obtaining a college degree. The findings of this study may be used to create resources for parents that did not attend college or those in lower socioeconomic status communities to more readily gain access to college information, which may aid in the enrollment process.